AMATÖR LİGLERDE OYNAYAN 14-17 YAŞ FUTBOLCULARIN ÖZGÜVEN DÜZEYLERİNİN İNCELENMESİ (HATAY İLİ ÖRNEĞİ) - AYTEKİN, ÜMRAN (Fırat Üniveristesi, 2019)
Araştırmanın amacı, amatör liglerde oynayan 14-17 yaş futbolcuların özgüven düzeylerini farklı değişkenler bazında incelemektir. Bu doğrultuda tarama modelindeki araştırmada veri toplama aracı olarak Akın (2007) tarafından geliştirilen 33 maddelik öz-güven ölçeği gönüllü katılımcılara uygulanmıştır. Ölçek; içsel özgüven ve dışsal özgüven olmak üzere iki alt boyuttan oluşmaktadır. Araştırma verilerinin değerlendirilmesinde istatistikî yöntem olarak frekans, yüzde dağılımları, ikili gruplar için Independent Samples t testi, çoklu gruplar için (Pearson Correlation testi) OneWay-ANOVA analizleri kullanılmıştır. Araştırma sonucunda; iç ve dış özgüven, toplam özgüven açısından lisanslı sporcu olanlar ile olmayanlar arasında anlamlı farklılık tespit edilmiştir (p<0.05). Lisanlı sporcu olanların tüm boyutlarda daha yüksek değerlere sahip olduğu tespit edilmiştir. Spor yaşı ile dış özgüven arasında anlamlı ilişki bulunurken (r=.133, p<0.05), spor yaşı ile iç özgüven ve toplam özgüven arasında anlamlı ilişki bulanamamıştır (p<0.05). Sonuç olarak, amatör liglerde oynayan 14-17 yaş futbolcuların özgüven düzeyleri, pek çok değişkenden etkilenebilmektedir. Araştırmada, futbol oynayan bireylerin, futbol oynamayan bireylere göre özgüven düzeylerinin daha yüksek olduğu sonucu ortaya çıkmıştır.

The aim of this study was to investigate the self-confidence levels of 14-17 year old football players playing in amateur leagues based on different variables. In this context, the self confidence scale developed by Akın (2007) and composed of 33 items was applied to volunteer participants attending as data collection tool in the survey based on descriptive scanning model. The scale I composed of two sub dimensions, namely inner self confidence and outer self confidence. Akın (2007) has calculated the reliability value of the scale he developed to be outer self confidence sub dimension. Frequency, percentage distribution, independent samples t test for dual groups and One Way-ANOVA analyses for multiple groups (Pearson Product Correlation test) were used as the statistical method for evaluation of the survey data. As a result of the survey; a significant difference between licensed athletes and the others in terms of inner and outer self confidence and overall self confidence (p<0.05). It has been observed that licensed athletes have higher values in all dimensions. While there was a significant relationship between the age of playing sports and outer self confidence (r=.133, p<0.05), there was no significant relationship between the age of playing sports and inner self confidence and overall self confidence (p<0.05). As a result, the level of self-confidence of 14-17 year old players playing in amateur leagues can be affected by many variables. In the study, it was found that the individuals who play football have higher self-confidence levels than those who do not play football.
Analysis of the self-confidence levels of 14-17 age soccer players playing in amateur leagues (sample of Hatay)
Keywords: Spor